IDENTIFIKASI BATAS SUB-CEKUNGAN HIDROKARBON MENGGUNAKAN ANALISIS SHD (SECOND HORIZONTAL DERIVATIVE) DAN SVD (SECOND VERTICAL DERIVATIVE) BERDASARKAN KORELASI DATA GAYABERAT DAN SEISMIK - Wuri Andari; Karyanto Karyanto; Riski Kurniawan (Engineering Faculty Universitas Lampung, 2019)
Gravity method generally can read the difference of rock density to identify subsurface structures. This research was conducted in Riau area with the aim of knowing fault and subsurface structure, and determining sub-basin boundary. Data processing was done by using spectral analysis, SHD and SVD analysis, and 2D modeling then later correlated with seismic section to find out the subsurface structure of research area. The results showed that the bouguer anomaly value had a range of values between 5.6 mGal to 33.2 mGal with a surface density of 1.95 g / cc. High anomaly were in the eastern region and low anomaly were in the NW - SE trending region. 6 low anomalies indicated as a sub-basin pattern were separated by a relatively high altitude area of North West Southeast. The average residual anomaly depth was about 2.3 km. Based on the 2D subsurface modeling results, there was layer structure from the youngest to eldest that were alluvial deposits, Petani Formation, Sihapas group and granitic rock as the base rock. The projected subsurface section to surface showed 5 sub-basins with basin width 4-12 km located in the sub-basin and fault indication area.